A Case Report of Hypertensive Emergency and Intracranial Hemorrhage Due to Intracavernosal Phenylephrine. (June 2019) - Palagiri, Raga Deepak Reddy; Chatterjee, Kshitij; Jillella, Anusha; Hammond, Drayton A.
Background: Intracavernosal injection of phenylephrine is a commonly used therapy for ischemic priapism and is typically well tolerated with few severe adverse side effects. We report a case of intracranial hemorrhage related to hypertensive emergency due to intracavernosal phenylephrine.Case Report: A 43-year-old Caucasian man with history of hypertension, diabetes mellitus type I, end-stage renal disease status post a combination kidney-pancreas transplant, and recurrent idiopathic priapism presented to emergency department with an episode of priapism. His home medications were lisinopril, metoprolol tartrate, mycophenolate mofetil, prednisone, sulfamethoxazole-trimethoprim, and tacrolimus. After local injection of 2 rounds (1 hour apart) of 100 µg phenylephrine into each corpus cavernosa, priapism resolved. Within 5 minutes, the patient had headaches, dyspnea, and excruciating chest pain. His blood pressure (BP) was noted to be 240/130 mm Hg but normalized spontaneously within few minutes. During this period, he developed new-onset right arm and leg weakness and found to have intracranial hemorrhage in the midbrain.Conclusion: A careful review for pharmacologic interactions should be performed prior to intracavernosal phenylephrine administration, and close monitoring should occur after its administration.